2009
DOI: 10.1111/j.1365-2133.2009.09146.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of beta human papillomaviruses in nonmelanoma skin cancer from organ transplant recipients and immunocompetent patients in the West of Scotland

Abstract: A wide spectrum of betaPV types was detected in our samples. Further characterization of betaPV in vivo is needed in order to determine the mechanisms by which the virus contributes to cutaneous carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…14,23,24,3038 SCC from immunosuppressed patients are more likely to carry HPV than SCC from immunocompetent patients (pooled ES 3.01, 95%CI 2.00–4.52, p<0.0001). There was minimal evidence of heterogeneity (I 2 =28.4%, Q = 15.37 (d.f.…”
Section: Resultsmentioning
confidence: 99%
“…14,23,24,3038 SCC from immunosuppressed patients are more likely to carry HPV than SCC from immunocompetent patients (pooled ES 3.01, 95%CI 2.00–4.52, p<0.0001). There was minimal evidence of heterogeneity (I 2 =28.4%, Q = 15.37 (d.f.…”
Section: Resultsmentioning
confidence: 99%
“…Seroepidemiological studies have associated skin cancer in organ transplant recipients with the presence of anti-b-HPV antibodies, and PCR-based studies have identified b-HPV DNA in over 80% of skin tumors from these patients. 22,[35][36][37][38][39][40][41][42][43] Despite these findings, a causal role of these viruses has been difficult to verify because of their ubiquitous prevalence in the general population and their absence in some cancers. 25,44 The major weakness of the available studies is that the proposed association is mostly based on the presence of viral DNA in tumor tissues or positive antibody responses.…”
mentioning
confidence: 99%
“…Novel beta HPV PsV types were designed according to HPV prevalence in NMSC of both immune-suppressed and immune—competent patients, and to provide at least one type representative of different beta HPV species [73]. In general, novel beta HPV PsV showed variable infectivity and not all were useful in vivo .…”
Section: Discussionmentioning
confidence: 99%